Racial Disparities in HIV Antiretroviral Medication Management are Mediated by Health Literacy - Drenna Waldrop-Valverde; Raphiel Jamale Murden; Ying Guo; Marcia Holstad; Raymond L. Ownby (SLACK Incorporated, 2018)
Background: Despite the availability of antiretroviral (ARV) therapy in the United States, only 30% of people living with HIV/AIDS (PLWH) in the US are virally suppressed. Nonadherence to ARVs remains the strongest correlate of viral suppression. African Americans (AA) living with HIV/AIDS remain disproportionately affected by this disease, and studies report a greater proportion of infections and deaths among this group. Objective: Earlier studies by this team and others have shown that health literacy (HL) may negatively influence disparities in health behaviors, including management of ARV prescriptions, between AA and non-AA PLWH. This current study expands these findings and tests whether HL may explain disparities in medication management among AA and non-AA PLWH and includes important covariates and measures of participants' actual medication regimens. Methods: PLWH were recruited from HIV care clinics in the greater metropolitan area of Atlanta, GA, and completed a face-to-face study visit. A total of 699 PLWH, 65% of whom were AA, completed this study visit. Assessment of knowledge and management of participants' actual medication regimens showed highly skewed responses, demonstrating accurate verbal descriptions of ARV prescription instructions. A measure of problem-solving (how to manage a mock ARV regimen) showed significantly different performance by race and that HL measures (both reading comprehension and numeracy) mediated this relationship. Key Results: Findings suggest that although PLWH may be able to verbally explain how they are supposed to take their ARV medication, challenges may arise with management issues (eg, determining need for a refill, counting pills to determine if a dose was missed) and that PLWH with low HL (who are disproportionately AA) may be at greater risk for mistakes. Other characteristics, such as cognitive impairment, were also shown to influence medication management. Conclusion: Attention to PLWH's potential for mismanagement of ARV and other medications is important to identify for educational interventions.